Excited and aroused: The predictive importance of simple choice process metrics - Steffen Q. Mueller; Patrick Ring; Maria Fischer (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2020)
We conduct a lottery experiment to assess the predictive importance of simple choice process metrics (SCPMs) in forecasting risky 50/50 gambling decisions using different types of machine learning algorithms as well as traditional choice modeling approaches. The SCPMs are recorded during a fixed pre-decision phase and are derived from tracking subjects' eye movements, pupil sizes, skin conductance, and cardiovascular and respiratory signals. Our study demonstrates that SCPMs provide relevant information for predicting gambling decisions, but we do not find forecasting accuracy to be substantially affected by adding SCPMs to standard choice data. Instead, our results show that forecasting accuracy highly depends on differences in subject-specific risk preferences and is largely driven by including information on lottery design variables. As a key result, we find evidence for dynamic changes in the predictive importance of psychophysiological responses that appear to be linked to habituation and resource-depletion effects. Subjects' willingness to gamble and choice-revealing arousal signals both decrease as the experiment progresses. Moreover, our findings highlight the importance of accounting for previous lottery payoff characteristics when investigating the role of emotions and cognitive bias in repeated decision-making scenarios.
Keywords: C44; C45; C53; D81; D87; D91; 330; Repeated decision making; Eye-tracking; Psychophysiological responses; Machine learning; Forecasting